Lipidomics-based study on the neuroprotective effect of geissoschizine methyl ether against oxidative stress-induced cytotoxicity. (10th May 2020) - Sun, Jiahong; He, Fajing; Gao, Yue; Zhou, Yanying; Zhang, Huizhen; Huang, Min; Bi, Huichang
Abstract: Ethnopharmacological relevance: Lipid homoeostasis is important for neurodevelopment, cell signaling and neurotransmission. Alteration of lipid metabolism has been demonstrated in many neurological disorders and neurodegenerative diseases. Geissoschizine methyl ether (GM) is an active alkaloid ingredient in the traditional Chinese medicine Uncaria hook . It has been shown that GM has strong potency in neuroprotective activity and GM reduces the production of reactive oxygen species by regulating glucose metabolism, which protects neurons against oxidative stress-induced cell death. However, it is unknown whether GM could regulate neuronal lipid metabolism during oxidative challenge. Aim of the study: The current study aimed to explore whether GM regulates lipid metabolism in oxidative damaged neurons and to determine the underlying mechanism involved in this neuro-protection. Materials and methods: Using a glutamate-induced oxidative toxicity model in mouse hippocampal neuronal cell line (HT-22 cells), we investigated the effect of GM on glutamate-induced lipid peroxidation, lipotoxicity and mitochondrial dysfunction. In order to clarify the mechanism underlying the neuroprotection by GM, lipid metabolomics was performed to investigate whether GM prevent oxidative stress-induced lipid metabolism disruption. Furthermore, the expression of lipid metabolism-related genes was measured. Results: The results show the protective effect of GM against oxidative stress through blocking glutamate-induced lipid peroxidation and lipotoxicity. Overall, lipidomics analysis revealed that glutamate treatment resulted in different extents of changes in a wide range of lipid classes such as fatty acids (FA), triacylglycerol (TG), sphingomyelin (SM), cardiolipin (CL), lysophosphatidylcholines (LPC). However, GM treatment can significantly reverse glutamate-induced lipids disorder to the homeostasis level. GM prevented the disruption of lipid metabolism by regulating the expression of lipid homeostasis related genes, which contributes to preserve mitochondrial function under oxidative damage. Conclusion: These findings clearly demonstrated a novel protective mechanism of GM against glutamate-induced oxidative toxicity in neurons via regulating lipid metabolism. GM may provide an effective approach for the prevention and treatment of oxidative damaged neurons. Graphical abstract: Image 1